การเปรียบเทียบการวินิจฉัยโรคข้อเข่า เสื่อมทางแพทย์แผนตะวันตกกับโรค ลมจับโปงแห้งเข่าทางแพทย์แผนไทย - สุวรรณไตรย์, ศุภกิจ; พันธ์เพ็ง, ธเนศพล; คำแก้ว, นันทิพัฒน์; สีรูปหมอก, ปิยาอร; อุดมเกียรติ, พัชรพล; โชติวิจิตร, อารีศักดิ์; อัครเสรีนนท์, ประวิทย์; เลาหพันธ์, ทวี (Siriraj Medical Bulletin, 2018)
Objective: To compare the diagnosis of osteoarthritis of the knee in western medicine and the Thai traditional medicine diagnosis of Lom-Jub-Pong-Hang-Kao (LJP). Methods: LJP criteria were applied to patients who were age > 50-year-old and seen in the orthopedic clinic for knee pain. After examination of Thai Traditional Medicine by the Thai Traditional Medicine practitioners, patients continued to receive standard western medicine treatment. Results: 163 patients were mostly female and age average of 63.04±8.5 years. The majority of patients who were diagnosed with osteoarthritis knee disease were also diagnosed with LJP in Thai traditional medicine (91.5%). Small proportion patients who had osteoarthritis knee were diagnosed with Lom-Plai-Patakhad-Kao (6.7%). There were two cases of non-osteoarthritis knee patients, one with tuberculosis of the knee, and the other was chondromalacia patella. They were diagnosed with Lom-Jub-Pong-Num-Kao and Lom-Plai-Patakhad-Kao,respectively. The diagnosis score demonstrated that osteoarthritis knee disease in western medicine was significantly associated with LJP in Thai traditional medicine (R2=0.029; p=0.036). Conclusion: The Thai traditional medicine diagnosis of LJP can accurately diagnose the majority of patients with osteoarthritis knee. However, the discrepancy in diagnosis still exists between the two practices which can lead to differences in treatment. Therefore, further studies need to examine the different entities of Thai traditional medicine diagnosis of knee pain in order to confirm their consistency.